Сказки Старого Лиса: [сборник сказок] / А. Толстой [и др.] - Андреев И. (Золотая серия, 1992)
Экземпляры: М/а ДБ (20110323) / Инвентарный номер: 97082 / Цена: 25.00 / Авт.знак: С 42 / ГРНТИ: 17.82 / ББК: 84(0)